Repeat pregnancies among adolescent mothers. - Gillmore, Mary Rogers; Lewis, Steven M.; Lohr, Mary Jane (Journal of Marriage & Family, 1997)
An event history analysis was conducted to examine rapidly repeated pregnancies among a sample of 170 teenagers who had experienced a nonmarital birth. Survey participants were school-aged teenagers from lower- to middle-income families who were recruited from health and social service agencies in an urban district of the Northwest. Participants were interviewed at five stages from pregnancy through 18 months postpartum. The problem behavior theory and the social development model were used to suggest distal variables that might be linked to repeated pregnancies, and as expected, two proximate variables—frequency of intercourse and contraceptive use—were significant indicators of repeated pregnancy in both univariate and multivariate models. The best fitting multivariate model included variables consistent with problem behavior theory, including a history of school troubles, drug use, fighting, and age at first birth.